The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.36761/hexagon.v3i2.1646
|View full text |Cite
|
Sign up to set email alerts
|

Nova Aryanto KELAYAKAN PEMASANGAN INSTALASI LISTRIK RUMAH TANGGA DAYA 900 VA USIA 20 TAHUN SESUAI PENGELOMPOKAN PENGUJIAN INSTALASI PERSYARATAN UMUM INSTALASI LISTRIK (PUIL) 2000 STUDI KASUS DI KECAMATAN TARANO KABUPATEN SUMBAWA

Abstract: Penelitian uji kelayakan instalasi listrik rumah tangga dibuat untuk mengetahui kelayakan instalasi listrik tegangan rendah daya 900 VA umur 20 tahun di Kecamatan Tarano. Komponen yang diteliti dalam uji kelayakan instalasi listrik rumah tangga meliputi perlengkapan, peralatan instalasi listrik, pengaman instalasi listrik yang di lihat dari kondisi fisiknya, meliputi ukuran dan jenis penampang yang digunakan, isolasi penghantar  dan pembumian.  Teknik analisis data yang digunakan yaitu teknik analisis deskript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, some damage is still found, such as termite attacks on switches, peeling cable connections, unequal power distribution, and inappropriate capacity use. For case studies with a building age of more than 10 years or more, the percentage obtained is very high compared to Santoso's research [24], where electrical installations in residential houses aged more than 15 years-old are 43.56%. In line with Santoso [24], Ali [25] found that residential electrical installations with an age of more than 15 years, only reached 26%.…”
Section: Electrical Componentsmentioning
confidence: 56%
“…However, some damage is still found, such as termite attacks on switches, peeling cable connections, unequal power distribution, and inappropriate capacity use. For case studies with a building age of more than 10 years or more, the percentage obtained is very high compared to Santoso's research [24], where electrical installations in residential houses aged more than 15 years-old are 43.56%. In line with Santoso [24], Ali [25] found that residential electrical installations with an age of more than 15 years, only reached 26%.…”
Section: Electrical Componentsmentioning
confidence: 56%
“…Didapatkan suatu kasus yang mana instalasi listrik untuk rumah tinggal tidak tertata dengan teratur dimana pemasangan instalasi listrik secara sembarangan tanpa memperhatikan estetika, kenyamanan, serta keselamatan penghuni bangunan tersebut [8]. Dalam hal ini peneliti melakukan test kepatutan terhadap instalasi listrik yang berada di keacamatan Tarano, Hasil daari test kepatutan suatu instalasi listrik yang dikatakan Jumlah kelayakan instalasi listrik di Kecamatan Tarano, yang dinyatakan memadai terdapat 54 rumah dan yang tidak memadai terdapat 24 rumah [9].…”
Section: Pendahuluanunclassified